2013
DOI: 10.1016/j.neuropharm.2012.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent male rats are less sensitive than adults to the anxiogenic and serotonin-releasing effects of fenfluramine

Abstract: Risk taking behavior increases during adolescence, which is also a critical period for the onset of drug abuse. The central serotonergic system matures during the adolescent period, and its immaturity during early adolescence may contribute to adolescent risk taking, as deficits in central serotonergic function have been associated with impulsivity, aggression, and risk taking. We investigated serotonergic modulation of behavior and presynaptic serotonergic function in adult (67–74 days old) and adolescent (28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 113 publications
4
27
0
1
Order By: Relevance
“…To address this question, we infused the 5HT-releasing agent fenfluramine (Arrant et al, 2013) into the lateral ventricle of adult mice (Figure 5N). Numbers of 5-bromo-2'-deoxyuridine (BrdU)-labeled cells and DCX+ neuroblasts significantly increased following 2-day infusion of fenfluramine, as compared to saline-infused controls (Figure 5O, P, S4E–P), suggesting 5HT induced an increase in proliferation and neurogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…To address this question, we infused the 5HT-releasing agent fenfluramine (Arrant et al, 2013) into the lateral ventricle of adult mice (Figure 5N). Numbers of 5-bromo-2'-deoxyuridine (BrdU)-labeled cells and DCX+ neuroblasts significantly increased following 2-day infusion of fenfluramine, as compared to saline-infused controls (Figure 5O, P, S4E–P), suggesting 5HT induced an increase in proliferation and neurogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Immature serotonergic system makes it vulnerable to stress even during early development (Spear, 2000;Arrant et al, 2013). As increased serotonin is associated with increased anxiety-related behaviour (Treit et al, 1993), decreased anxietyrelated behaviour, observed in the pups of sleep-deprived mothers, may be due to an immature serotonergic system.…”
Section: Elevated Plus Maze Testmentioning
confidence: 99%
“…Species, strain, and methodological differences may account for discrepancies between studies. Adolescent male rats (around PN28) have been reported as having either more or less anxiety-like behavior than adults in the LD test, and a study of adolescent male mice found greater anxiety-like behavior than adults [1821]. Early adolescent male rats (PN28) do not exhibit anxiety-like behavior in the SI test, a behavior that does not mature until after the onset of puberty [22].…”
Section: Introductionmentioning
confidence: 99%
“…The LD test has been used to assess age differences in the response to stress and anxiogenic drugs in adolescent versus adult male rats [1921]. Adolescents have been reported as exhibiting greater anxiogenic responses to stress, but are less sensitive to the anxiogenic effects of drugs targeting the endocannabinoid and serotonergic systems [1921]. …”
Section: Introductionmentioning
confidence: 99%